2020
DOI: 10.1016/j.sapharm.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The development of a foundation-level pharmacy competency framework: An analysis of country-level applicability of the Global Competency Framework

Abstract: Background The importance and usefulness of competency frameworks (CFs) in pharmacy professional development is recognised globally. However, there is no national CF for pharmacists in Japan yet. Objective This study was conducted to measure the level of relevance of behavioural statements of the International Pharmaceutical Federation (FIP) Global Competency Framework (GbCF) to Japanese foundation-level pharmacy practice, aiming for developing a national framework for foundation-level pharmacists in Japan. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Following this first step for national CF development, several steps for future work include; 1) consensus development panels and Delphi techniques for identifying and refining competency clusters and competencies for general and service-specific levels; 2) national survey for validating applicability of the CFs; and 3) expert panels for final validation. 22,34,35,49 Using qualitative data collection technique to gather firsthand data is a strength of this CF development, but with major limitation in sample selection. Since findings were harvested from informants who were experts in all area of professional practices, there were limited numbers of key informants from private hospitals and community pharmacies.…”
Section: 20mentioning
confidence: 99%
“…Following this first step for national CF development, several steps for future work include; 1) consensus development panels and Delphi techniques for identifying and refining competency clusters and competencies for general and service-specific levels; 2) national survey for validating applicability of the CFs; and 3) expert panels for final validation. 22,34,35,49 Using qualitative data collection technique to gather firsthand data is a strength of this CF development, but with major limitation in sample selection. Since findings were harvested from informants who were experts in all area of professional practices, there were limited numbers of key informants from private hospitals and community pharmacies.…”
Section: 20mentioning
confidence: 99%
“…-One institutional framework for cancer services; 69 and -Six other national frameworks specific for heart failure, 70 diabetes, 71 pharmacists with special interest, 72 medicines information, 73 critical care, 74 and medicines use review and prescribing intervention services. 75 Also included in this review were 22 studies that evaluated validity and/or applicability to practice of a competency framework in pharmacy 9,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] (this was in addition to the articles by Kennie-Kaulbach et al 59 and Carrington et al 69 that also reported the validation results of their respective frameworks) (Table 3). Of the 22 studies, the majority (n=10, 45%) were articles that evaluated the validity/applicability of a generic, sector/role-related, or specialty-specific framework in United Kingdom 76,80-82,88 , Croatia 9,93 , and other countries in Europe 83,86,94 (Table 3); Others were studies conducted in Australia 69,78,84,91 (Western Pacific); Japan 90 , Kuwait 89 (Eastern Mediterranean); USA 87 , Canada 59 (the Americas); Thailand 79 (South East Asia); and Africa (included Ghana, Kenya, Nigeria, South Africa and ten other countries in the region) 85…”
Section: IImentioning
confidence: 99%
“…Framework validation mainly aimed to evaluate perception of applicability to practice of the identified competencies. This primarily involved profession-wide consultation conducted via online (web-based 15,20,77,83,85,[89][90][91] and email 76 ) or postal 79,82 surveys, as well as qualitative interviews. 54,81 Ranking of the identified competencies and qualitative comments by practitioners were proxy measures of applicability to practice for most of the frameworks.…”
Section: Validity and Applicability To Practice Of Pharmacy-related C...mentioning
confidence: 99%
“…However, competency-based education is increasingly being referred to as a 'global education policy' (Tromp, 2018). Internationally, professions are various stages of implementing entry-to-practice competence frameworks (e.g., Arakawa, Yamamura, Duggan & Bates, 2019;Patel, Tonni, Gadbury-Amyot, van der Vleuten & Escudier, 2018). Given the important nuances in the above conceptions of competence, it is possible to see how diverse professions--with diverse ways of thinking and approaches to solving complex problems--might begin to talk about this construct in different ways as they undergo educational reform.…”
Section: The Research Problemmentioning
confidence: 99%